WAGE AND LABOR SURVEY FOR SPOTSWOOD, NEW JERSEY (Tufts Archival Research Center, 2007)
Results from a wage and labor survey done in Spotswood, New Jersey. Contains the key points from conversations with people from different industries in New Jersey.